Sistem Informasi Distribusi PT Sulung Ekspedisi - Steven Jonathan Hans; Yulia Yulia; Adi Wibowo (Jurnal Infra, 2017)
PT Sulung Ekspedisi is one of the companies engaged in the service of the expedition. Services provided in the form of delivery of goods through land service with Surabaya route to Babat, Probolinggo, Tuban, and surrounding areas. The company also cooperates with PT Heinz ABC in assisting the distribution of goods coming from factories to other factories or to storage warehouses. The number of types of goods and routes aimed at encouraging PT Sulung Ekspedisi requires a system that can support their work. At this time the system used by the company using a manual system, in this case the recording of both the transfer of information between thecashier and other divisions still use the recording through the paper media. PT Sulung Expedisi does not currently have a system that their customers can use to check whether the items they are sending are in the acceptance, travel, or received by the recipient. Currently to do so the customer can only use the phone as a medium. Apilkasi Distribution Information System PT Sulung Expedisi is made to meet the needs of the company. Features owned by the application, among others, manage the data master company such as employee data, agency data, tariff data, record and make the delivery notes as a valid proof of delivery, record and make a letter as a supporting document, to record in a simple financial company such as recording Income and expenses. This application also features a tracking feature that can know the delivery status and location of the fleet during the delivery process. Fleet position obtained through GPS system originating mobile device applications brought by the driver during the process of delivery of goods. The results obtained based on testing and distributed questionnaires found that the overall application has been able to run well and able to meet the needs of companies in recording company data computerized. But there are small errors such as GPS System that is less accurate so it has not been able to provide the fleet location to the fullest.